University extension practices for the integration of environmental knowledge of park-ranger students and rural school students in the province of Córdoba, Argentina (Cuadernos de Extensión Universitaria de la UNLPam, 2026)
University extension has been developed for many years by academic institutions as a core function, alongside teaching and research activities, related to social needs, and recently, to ecological and environmental aspects. In this article, we present the systematization of the exchange of ecological and environmental knowledge from the university extension project “Helping to the Native Forest” of the University Technical Program in Park-Ranger Studies, Faculty of Tourism an Environment, Provincial University of Córdoba, Argentina, between 2018 and 2023. The activities of this project were carried out within the university academic sphere and also with other external institutions, in pre and post-pandemic periods. We achieved the exchange of ecological and environmental knowledge among university students from different faculties and rural schools, with results such as the development of interactive learning materials, a logo and workshops related to the topic. This process can be enriched and improved by taking into account the experiences gained to date.
Keywords: park rangers; curriculum integration; university extension; environmental knowledge; native forest